ANALISIS PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP RETURN SAHAM BANK DI BURSA EFEK INDONESIA - Daneil Nemba Dambe (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aim of this study was to examine the effect of liquidity ratio representedbyLoan to Deposit Ratio (LDR), and profitability ratiorepresented by Return on Assets (ROA) on Bank stock returns (Rt) in Indonesia Stock Exchange, simultaneously or partially. This was an associative study using the quantitative approach. Financial statistic data were obtained from Indonesia Bank, ICMD (Indonesian Capital Market Directory) from theperiod of 2011 to 2015. The population consisted of 38 banks and the total sample consisted of 26 banks which wasselected by using purposive sampling. The data were analyzedby using Multiple Regression Analysis with Classical Assumption Test and performed with SPSS Statistics. The hypotheses were tested by using F test, t test, and regression coefficient test (R2adj). The results indicate that liquidity ratio variable represented by loan to deposit ratio (LDR), and profitability ratio represented by Return on Assets (ROA) simultaneously have a no significant effect on stock return. Partially, profitability ratio is the only variable represented by a Return on Assets (ROA), significantlyaffectsbank stock returns.